Reaching Beyond Democracy in Educational Policy Analysis. (January 2016) - Patel, Leigh
Educational policy analyses have tended toward either the impact of policies on student achievement or the furthering of progressive ideals, regularly theorized through concepts of democracy. In this theoretical essay, I suggest that democracy has become a vehicle for cauterized projects of individualized and contingent state status rather than decolonization and material transformation. This is due not to intentional disregard but to limited epistemic reach. Specifically, I address the ways that the tenets of democratic theory cannot address population-level stratification and racialization of space. I close with how a critique of the limits of democratic ideals can open up space for more robust epistemological groundings.